UV viscosity-reducing adhesive for wafer cutting PO protective film and preparation method of UV viscosity-reducing adhesive
By using UV detoxifying glue that combines unsaturated branched acrylate polymer with photoinitiator and curing agent, the problems of insufficient adhesive strength of the traditional protective film and insufficient peel strength of the existing UV detoxifying glue are solved, and efficient wafer cutting and good high-temperature stability are achieved.
Patent Information
- Application Number
- CN202411834306.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-29
AI Technical Summary
Inadequate adhesion of traditional protective films during wafer cutting leads to cutting offset and stuttering, and the existing UV adhesives have insufficient peel strength and stability.
UV adhesive reducing glue is prepared by acrylate polymer containing unsaturated branched chains by combining with photoinitiator and curing agent through radical polymerization and graft modification reaction, and the graft amount of functional crosslinked monomer is controlled to adjust the peel strength and high temperature stability.
High peel strength before UV curing is achieved, the peel strength after UV curing drops to near 0, and there is no residual glue after high temperature treatment, meeting the requirements for use of wafer cutting PO protective film.
Smart Images

Figure BDA0005186298470000051 
Figure BDA0005186298470000052 
Figure BDA0005186298470000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pressure-sensitive adhesives, and in particular to a UV viscosity-reducing adhesive for a wafer cutting PO protective film and a preparation method thereof. Background Art
[0002] Traditional blue film (also known as electronic grade tape) plays a certain supporting and protective role in the wafer cutting process. However, with the improvement of process automation, it is necessary to have good supporting force and picking rate after the process is completed, which puts higher requirements on the use of adhesive materials. In actual application, after removing the release film, the traditional protective film composed of release film, PO film and intermediate adhesive layer is pasted on the wafer. The intermediate adhesive layer adheres to the wafer. When its bonding force is weak, the high-speed rotation of the cutting knife will cause cutting deviation and peripheral lifting.
[0003] UV viscosity-reducing adhesive is a kind of adhesive that can cure quickly under UV light curing to form a strong bonding effect. Further, under ultraviolet light, the adhesive strength will drop sharply. Its characteristics can solve the problem that the adhesion of traditional protective films is too high or too low and cannot meet processing requirements. Currently, the adhesive layer on the market is an acrylate adhesive with unsaturated double bonds in the side chain. As a protective film glue, acrylate adhesive can play a protective role during cutting, but after cutting, it still has a high adhesion, which is difficult to remove, easy to damage the wafer, and difficult to operate. In addition, the high temperature resistance, chemical resistance and processing performance of the adhesive material still need to be improved.
[0004] Chinese patent CN119039890A discloses a UV viscosity-reducing adhesive liquid, a UV viscosity-reducing film and a display screen module, which utilizes a polyacrylic resin and a methoxy-containing silane coupling agent to achieve reinforcement and viscosity enhancement of the UV viscosity-reducing film. Chinese patent CN118652657A discloses a polyurethane-based UV viscosity-reducing adhesive based on dimer acid and a preparation method thereof, which introduces a terminal hydroxy dimer acid-methacrylate glycidyl ester trimer prepolymer into the UV viscosity-reducing adhesive to improve the 180° peel strength of the UV viscosity-reducing adhesive before UV irradiation and the viscosity-reducing effect after UV irradiation. However, these prior arts either have a low peel strength before UV irradiation, or a high peel strength after UV irradiation, or have poor stability and chemical resistance, and none of them solve the above technical problems at the same time.
[0005] Under such circumstances, there is an urgent need to provide a wafer cutting PO protective film adhesive having good adhesion, high temperature resistance, acid and alkali resistance, cutting fluid resistance, no residual glue, no overflow of glue and other properties. Summary of the invention
[0006] In view of the defects and shortcomings in the prior art, the present invention provides a photothermal curing UV viscosity-reducing adhesive for semiconductor wafer cutting PO (polyolefin) protective film. After the adhesive is coated on the surface of the PO film substrate and cured to form an adhesive layer, it has excellent acid and alkali resistance, high temperature resistance, cutting fluid resistance and high adhesion to wafers. It can replace the traditional acrylate thermal curing adhesive layer and meet market index requirements.
[0007] The first aspect of the present invention provides a UV viscosity-reducing adhesive for wafer cutting PO protective film, and the raw materials for preparing the UV viscosity-reducing adhesive include component A and component B:
[0008] In terms of mass percentage, the component A includes 97-99.5% of an acrylate polymer and the remainder of a photoinitiator;
[0009] The B component includes a curing agent.
[0010] In some preferred embodiments, the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0011] In some preferred embodiments, the raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst and organic solvent. The present invention prepares the acrylic ester polymer containing unsaturated side chains by free radical polymerization combined with graft modification reaction of the above raw materials, and the prepared product has a solid content of 20-40%.
[0012] In some preferred embodiments, the raw materials for preparing the acrylic ester polymer further include a co-solvent, and the co-solvent can be exemplified by toluene.
[0013] In some preferred embodiments, the acrylic monomer includes at least one of methyl acrylate, ethyl acrylate, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, methacrylic acid, 2-ethylhexyl acrylate, methyl methacrylate, and butyl methacrylate.
[0014] More preferably, the acrylic monomers include isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate and methacrylic acid; the weight ratio of isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate and methacrylic acid is (10-15):(8-12):(1-4):(2-5):(1-3); preferably 12.8:10.2:2.3:3:1.5.
[0015] Preferably, the amount of the acrylic acid monomer added is 20-50% of the total mass of the acrylic acid monomer, the initiator and the organic solvent; more preferably 25-40%.
[0016] The initiator can be listed as azobisisobutyronitrile, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, persulfate, etc.; preferably azobisisobutyronitrile.
[0017] Preferably, the added amount of the initiator accounts for 0.05-0.3% of the total mass of the acrylic acid monomer, the initiator and the organic solvent; more preferably, it is 0.2%.
[0018] The organic solvent can be listed as toluene, acetone, ethyl formate, ethyl acetate, ethanol, butanol, n-hexane, dichloromethane, ethyl ether, tetrahydrofuran, dimethylformamide, isooctyl ester, ethylene glycol methyl ether, etc.; preferably at least one of toluene, acetone and ethyl acetate.
[0019] Preferably, the amount of the organic solvent added is 50-80% of the total mass of the acrylic acid monomer, the initiator and the organic solvent; more preferably 60-75%.
[0020] In some preferred embodiments, the functional cross-linking monomer is an acrylate monomer containing both an unsaturated double bond and a hydroxyl structure.
[0021] More preferably, the functional cross-linking monomer is pentaerythritol triacrylate or hydroxyethyl acrylate.
[0022] Preferably, the added amount of the functional cross-linking monomer accounts for 10-30% of the total mass of the functional cross-linking monomer, diisocyanate, catalyst and co-solvent; more preferably, 15-25%.
[0023] The diisocyanate may be toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (H12MDI), hexamethylene diisocyanate (HDI), lysine diisocyanate (LDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), etc., preferably isophorone diisocyanate (IPDI).
[0024] Preferably, the added amount of the diisocyanate accounts for 40-60% of the total mass of the functional cross-linking monomer, diisocyanate, catalyst and co-solvent; more preferably, 45-55%.
[0025] Examples of the catalyst include dibutyltin dilaurate, stannous octoate, triethylenediamine and its derivatives, dimethylcyclohexylamine, and the like, preferably dibutyltin dilaurate.
[0026] Preferably, the added amount of the catalyst accounts for 0.01-1% of the total mass of the functional cross-linking monomer, diisocyanate, catalyst and co-solvent.
[0027] In some preferred embodiments, the steps of preparing the acrylic acid ester polymer include:
[0028] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate oligomer;
[0029] (2) mixing a functional cross-linking monomer with a diisocyanate and a catalyst to prepare a polyurethane acrylate prepolymer containing an unsaturated double bond and an isocyanate group;
[0030] (3) The products of step (1) and step (2) are mixed and reacted to generate an acrylate polymer containing unsaturated side chains.
[0031] In some preferred embodiments, when the functional cross-linking monomer is pentaerythritol triacrylate, in the step (3), the products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:(0.15-0.25); more preferably, the molar ratio is 1:2.
[0032] In some preferred embodiments, when the functional cross-linking monomer is hydroxyethyl acrylate, in the step (3), the products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:(0.65-0.95); more preferably, the molar ratio is 1:8.
[0033] Preferably, the co-solvent is added in step (2).
[0034] UV adhesive has the characteristics of high adhesion during the cutting process in the heat curing stage, and can replace traditional protective adhesive films. This is because after the UV adhesive is completed, the double bonds undergo a rapid free radical polymerization reaction under the action of the light source. At this time, the double bond polymerization process will produce a shrinkage effect, which will cause the adhesion between the UV adhesive and the wafer to drop rapidly. At the same time, after the double bonds on the side chain are polymerized, the molecular weight of the UV adhesive rises sharply, and the cross-linking density is significantly improved, so that the two-dimensional cross-linking structure becomes a three-dimensional cross-linking structure. The hardness and cohesion of the adhesive layer have been greatly improved, thereby reducing the interaction between the UV adhesive and the wafer. Under the synergistic effect of double bond shrinkage and increased hardness, the PO protective film prepared by the UV adhesive can be quickly detached from the wafer.
[0035] The present invention selects pentaerythritol triacrylate and hydroxyethyl acrylate as functional crosslinking monomers, and reacts them with isophorone diisocyanate respectively to prepare polyurethane acrylate prepolymers containing unsaturated double bonds and isocyanate groups, which are respectively recorded as oligomer A or oligomer B. Through experimental exploration, when the molar ratio of -OH to -NCO during the reaction is different, that is, the grafting amount of oligomer A or oligomer B in the acrylate polymer is different, the peel strength of the final UV viscosity-reducing adhesive before and after UV curing has obvious differences, and the high-temperature stability of the UV viscosity-reducing adhesive also has advantages and disadvantages; only by maintaining an appropriate molar ratio, the final UV viscosity-reducing adhesive can reduce the peel strength to close to 0 after UV curing, be easy to peel, and have no residual adhesive after high-temperature treatment.
[0036] The structural formula of oligomer A is as follows:
[0037]
[0038] The structural formula of oligomer B is as follows:
[0039]
[0040] In some preferred embodiments, the photoinitiator includes a free radical polymerization photoinitiator, which can be listed as 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2,4,6-trimethylbenzoyldiphenylphosphine (TPO), 2-hydroxy-2-methyl-1-phenylpropanone (photoinitiator 1173), benzoin dimethyl ether (BDK), 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone (photoinitiator 907), 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone (photoinitiator 369), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), and 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone (photoinitiator 127).
[0041] More preferably, the photoinitiator comprises 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine; the weight ratio of 1-hydroxycyclohexyl phenyl ketone to 2,4,6-trimethylbenzoyl diphenoxyphosphine is 1:(1.1-1.5).
[0042] Preferably, the added amount of the curing agent is 0.5-3% of the mass of component A; more preferably 1.5%.
[0043] In some preferred embodiments, the curing agent includes an isocyanate oligomer.
[0044] More preferably, the isocyanate oligomer comprises a compound of a hydrophilic aliphatic polyisocyanate and an aromatic polyisocyanate.
[0045] As an example of the hydrophilic aliphatic polyisocyanate, Covestro 3100 can be cited.
[0046] Bayer L-75 can be cited as an example of the aromatic polyisocyanate.
[0047] Preferably, the mass ratio of the hydrophilic aliphatic polyisocyanate to the aromatic polyisocyanate is 1:(2-5).
[0048] In some preferred embodiments, the reaction temperature of step (1) is 75-85°C, and the reaction time is 7-10h.
[0049] In some preferred embodiments, the reaction temperature of step (2) is 35-45°C, and the reaction time is 5-7h.
[0050] The second aspect of the present invention provides a method for preparing a UV viscosity-reducing adhesive for wafer cutting PO protective film, and the preparation steps of the UV viscosity-reducing adhesive include: adding an acrylate polymer and a photoinitiator to a reactor in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain a UV viscosity-reducing adhesive product.
[0051] Preferably, the preparation process of the UV viscosity-reducing adhesive is carried out under yellow light conditions.
[0052] Beneficial effects:
[0053] The present invention provides a UV viscosity-reducing adhesive for wafer cutting PO protective film and a preparation method thereof, which has the following advantages:
[0054] (1) The present invention prepares a self-made acrylic ester polymer containing unsaturated side chains, which reacts with a photoinitiator and a curing agent to generate a UV viscosity-reducing adhesive with flexible and adjustable peel strength and good processing performance. The obtained UV viscosity-reducing adhesive can reduce the deviation rate of wafer cutting, and avoid corrosion and residual adhesive contamination of the wafer caused by acid and alkali liquids, cutting fluids and high temperatures during the cutting process, thereby improving the yield of the wafer.
[0055] (2) The present invention specifically selects pentaerythritol triacrylate or hydroxyethyl acrylate as a functional cross-linking monomer, and reacts with diisocyanate and acrylate prepolymer to graft unsaturated bonds and isocyanate groups into the acrylate polymer structure. The resulting adhesive material can maintain a high peel strength before UV treatment, and the peel strength drops rapidly to near 0 after UV treatment, thereby achieving both firm bonding and complete separation from the substrate when peeling is required, and can well meet the use requirements of wafer cutting PO protective film.
[0056] (3) The present invention controls the grafting amount of the functional cross-linking monomer during the reaction process, taking into account the initial peel strength of the adhesive, the degree of peel strength reduction after UV curing and the high-temperature stability to the greatest extent. The peel strength of the obtained UV viscosity-reducing adhesive reaches more than 1000g / 25cm before UV curing, and the peel strength is reduced to less than 0.1g / 25cm after UV curing. There is no residual adhesive when it is removed after being treated at 180°C for 2h. The comprehensive performance of the UV viscosity-reducing adhesive is good.
[0057] (4) The present invention adopts a specific UV viscosity-reducing adhesive formula, especially the reaction raw material design of acrylate prepolymer and polyurethane acrylate prepolymer, so that the polymerization systems have good compatibility and maintain appropriate reaction freedom, thereby generating a UV viscosity-reducing adhesive with appropriate adhesive hardness and debonding performance, effectively solving the technical problem that the acrylate adhesive still has a high adhesion after cutting, is difficult to remove, and is easy to damage the wafer.
[0058] (5) The UV viscosity-reducing adhesive of the present invention can be used to prepare a wafer cutting PO protective film by, for example, transfer coating, etc., so as to be used in coating production and subsequent wafer cutting. The raw materials of the present invention are easily available, the preparation process is simple, and high-quality electronic products can be produced while meeting mass production requirements. It has positive significance in the field of semiconductor industrial production and has broad application prospects. DETAILED DESCRIPTION
[0059] Note: Unless otherwise specified, the raw materials involved in the present invention are commercially available.
[0060] Example
[0061] Example 1
[0062] In a first aspect, the present embodiment provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0063] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0064] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0065] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0066] Based on the total mass of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 20.7% pentaerythritol triacrylate, the diisocyanate is 49.23% isophorone diisocyanate, the catalyst is 0.07% dibutyltin dilaurate, and the cosolvent is 30% toluene.
[0067] The preparation steps of the acrylic acid ester polymer include:
[0068] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0069] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer A) containing an unsaturated double bond and an isocyanate group;
[0070] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:0.8 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0071] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0072] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0073] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0074] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0075] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0076] The second aspect of this embodiment provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0077] Example 2
[0078] In a first aspect, the present embodiment provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0079] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0080] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0081] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0082] Based on the total weight of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 24% hydroxyethyl acrylate, the diisocyanate is 45.22% isophorone diisocyanate, the catalyst is 0.8% dibutyltin dilaurate, and the cosolvent is 29.98% toluene.
[0083] The preparation steps of the acrylic acid ester polymer include:
[0084] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0085] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer B) containing an unsaturated double bond and an isocyanate group;
[0086] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:0.1 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0087] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0088] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0089] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0090] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0091] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0092] The second aspect of this embodiment provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0093] Comparative Example 1
[0094] In a first aspect, the comparative example provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0095] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0096] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0097] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0098] Based on the total mass of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 20.7% pentaerythritol triacrylate, the diisocyanate is 49.23% isophorone diisocyanate, the catalyst is 0.07% dibutyltin dilaurate, and the cosolvent is 30% toluene.
[0099] The preparation steps of the acrylic acid ester polymer include:
[0100] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0101] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer A) containing an unsaturated double bond and an isocyanate group;
[0102] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:0.1 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0103] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0104] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0105] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0106] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0107] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0108] The second aspect of this comparative example provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain the UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0109] Comparative Example 2
[0110] In a first aspect, the comparative example provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0111] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0112] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0113] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0114] Based on the total mass of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 20.7% pentaerythritol triacrylate, the diisocyanate is 49.23% isophorone diisocyanate, the catalyst is 0.07% dibutyltin dilaurate, and the cosolvent is 30% toluene.
[0115] The preparation steps of the acrylic acid ester polymer include:
[0116] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0117] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer A) containing an unsaturated double bond and an isocyanate group;
[0118] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:0.3 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0119] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0120] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0121] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0122] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0123] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0124] The second aspect of this comparative example provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain the UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0125] Comparative Example 3
[0126] In a first aspect, the comparative example provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0127] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0128] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0129] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0130] Based on the total weight of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 24% hydroxyethyl acrylate, the diisocyanate is 45.22% isophorone diisocyanate, the catalyst is 0.8% dibutyltin dilaurate, and the cosolvent is 29.98% toluene.
[0131] The preparation steps of the acrylic acid ester polymer include:
[0132] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0133] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer B) containing an unsaturated double bond and an isocyanate group;
[0134] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:1 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0135] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0136] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0137] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0138] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0139] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0140] The second aspect of this comparative example provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain the UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0141] Comparative Example 4
[0142] In a first aspect, the comparative example provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0143] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0144] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0145] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0146] Based on the total weight of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 24% hydroxyethyl acrylate, the diisocyanate is 45.22% isophorone diisocyanate, the catalyst is 0.8% dibutyltin dilaurate, and the cosolvent is 29.98% toluene.
[0147] The preparation steps of the acrylic acid ester polymer include:
[0148] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0149] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer B) containing an unsaturated double bond and an isocyanate group;
[0150] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:0.6 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0151] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0152] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0153] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0154] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0155] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0156] The second aspect of this comparative example provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain the UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0157] Comparative Example 5
[0158] In a first aspect, the comparative example provides a UV viscosity-reducing adhesive for wafer cutting PO protective film. The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B.
[0159] In terms of mass percentage, the component A includes 98.5% of an acrylate polymer and 1.5% of a photoinitiator; the acrylate polymer is an acrylate polymer containing unsaturated side chains.
[0160] The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst, organic solvent and co-solvent.
[0161] Based on the total mass of acrylic monomer, initiator and organic solvent, the acrylic monomer includes 12.8% isooctyl acrylate, 10.2% butyl acrylate, 2.3% hydroxyethyl acrylate, 3% hydroxypropyl methacrylate and 1.5% methacrylic acid; the initiator is 0.2% azobisisobutyronitrile; the organic solvent is 45.65% ethyl acetate, 9.35% toluene and 15% acetone.
[0162] Based on the total weight of the functional cross-linking monomer, diisocyanate, catalyst and cosolvent, the functional cross-linking monomer is 24% hydroxyethyl acrylate, the diisocyanate is 45.22% isophorone diisocyanate, the catalyst is 0.8% dibutyltin dilaurate, and the cosolvent is 29.98% toluene.
[0163] The preparation steps of the acrylic acid ester polymer include:
[0164] (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate prepolymer;
[0165] (2) mixing a functional cross-linking monomer with a diisocyanate, a catalyst, and a cosolvent to prepare a polyurethane acrylate prepolymer (oligomer B) containing an unsaturated double bond and an isocyanate group;
[0166] (3) The products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:0.2 to generate an acrylate polymer containing unsaturated branches; the solid content of the reaction product is 30 wt %.
[0167] The reaction temperature of step (1) is 80°C and the reaction time is 9h; the reaction temperature of step (2) is 45°C and the reaction time is 6h.
[0168] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine, and the weight ratio is 45:55.
[0169] The B component includes a curing agent, and the added amount of the curing agent is 1% of the mass of the A component.
[0170] The curing agent is a compound of hydrophilic aliphatic polyisocyanate (Covestro 3100) and aromatic polyisocyanate (Bayer L-75).
[0171] The mass ratio of Covestro 3100 and Bayer L-75 is 1:3.
[0172] The second aspect of this comparative example provides a method for preparing the above-mentioned UV viscosity-reducing adhesive, and the preparation steps include: adding an acrylate polymer and a photoinitiator to a reaction kettle in sequence, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; when using, mixing component A and component B according to the formula amount to obtain the UV viscosity-reducing adhesive; the preparation process is carried out under yellow light conditions.
[0173] Performance Testing
[0174] Preparation method of adhesive film: The UV anti-viscosity adhesive prepared in Examples 1-2 and Comparative Examples 1-5 was coated on the surface of a 150 μm PO film by blade coating, the solvent was dried at 120°C for 2 min, a release film was applied, and then the film was placed in an oven at 65°C for 48 hours to prepare a UV anti-viscosity film. The UV anti-viscosity film was treated with UV (light energy: 300 mJ), and the adhesive material properties before and after the UV treatment were tested; the test results are shown in Table 1 below.
[0175] The peel strength is tested with reference to the 180° peel strength test method in the national standard GB / T 2792-2014.
[0176] Acid resistance: The prepared UV adhesive film was placed in a 40 wt% hydrofluoric acid aqueous solution for 30 min, and then taken out to observe whether penetration occurred.
[0177] Alkali resistance: The prepared UV adhesive film was placed in a 50 wt% sodium hydroxide aqueous solution for 60 min, and then taken out to observe whether penetration occurred.
[0178] Cutting fluid resistance: Place the prepared UV film in cutting fluid (specifically Huayi Blue Sky HX-8000 product, the main component of which is polyethylene glycol) for 30 minutes, take it out and observe whether penetration occurs.
[0179] Table 1. UV viscosity-reducing adhesive performance test results
[0180]
[0181]
[0182] It can be seen from Table 1 that the UV viscosity-reducing adhesive obtained in Example 1 and Example 2 has a high peel strength before UV curing, and its peel strength is significantly reduced after UV curing, and it can maintain good adhesion, high temperature resistance and chemical resistance; while the UV viscosity-reducing adhesives of Comparative Examples 1-5 all show varying degrees of degradation. Specifically, the peel strength of the adhesive in Comparative Example 1 is still high after UV curing, which is not conducive to peeling. It is speculated that when the amount of PDI grafting is small, the double bond content is small, and the peeling force of the adhesive material after illumination is difficult to drop to a level close to 0. Comparative Examples 2 and 3 both show that there is still some residual adhesive after high-temperature treatment. It is speculated that when the amount of oligomer A and oligomer B added is too much, the presence of small molecule cross-linking monomers destroys the cohesion of the acrylate polymer, and the stability of the adhesive material is poor, resulting in residual adhesive after high-temperature treatment. The peel strength of Comparative Example 4 is still high after UV curing. It is speculated that when the amount of oligomer B grafting is small, the double bond content is small, and the double bond shrinkage force is insufficient, so the degree of reduction in the peel strength of the UV viscosity-reducing adhesive is small. In comparative example 5, the adhesive peeling strength is still high after UV curing, and there is still residual adhesive after high-temperature treatment. It is speculated that when the grafting amount G of oligomer B is too small, the double bond content is small, and the cross-linking density of the adhesive is low, which makes it difficult to reduce the adhesive peeling force after light exposure, and residual adhesive is left after high-temperature treatment.
Claims
1. A UV viscosity-reducing adhesive for wafer cutting PO protective film, characterized in that: The raw materials for preparing the UV viscosity-reducing adhesive include component A and component B: In terms of mass percentage, the component A includes 97-99.5% of an acrylate polymer and the remainder of a photoinitiator; the component B includes a curing agent; The acrylic acid ester polymer is an acrylic acid ester polymer containing unsaturated side chains.
2. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 1, characterized in that: The raw materials for preparing the acrylic ester polymer include: acrylic acid monomer, functional cross-linking monomer, initiator, diisocyanate, catalyst and organic solvent; The functional cross-linking monomer is an acrylate monomer containing both an unsaturated double bond and a hydroxyl structure.
3. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 2, characterized in that: The acrylic monomer includes at least one of methyl acrylate, ethyl acrylate, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, methacrylic acid, 2-ethylhexyl acrylate, methyl methacrylate, and butyl methacrylate.
4. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 3, characterized in that: The acrylic monomers include isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate and methacrylic acid; the weight ratio of isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate and methacrylic acid is (10-15): (8-12): (1-4): (2-5): (1-3).
5. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 2, characterized in that: The functional cross-linking monomer is pentaerythritol triacrylate or hydroxyethyl acrylate.
6. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 5, characterized in that: The preparation steps of the acrylic acid ester polymer include: (1) mixing acrylic acid monomer, initiator and organic solvent to react and prepare acrylate oligomer; (2) mixing a functional cross-linking monomer with a diisocyanate and a catalyst to prepare a polyurethane acrylate prepolymer containing an unsaturated double bond and an isocyanate group; (3) The products of step (1) and step (2) are mixed and reacted to generate an acrylate polymer containing unsaturated side chains.
7. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 6, characterized in that: When the functional cross-linking monomer is pentaerythritol triacrylate, in step (3), the products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:(0.15-0.25).
8. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 6, characterized in that: When the functional cross-linking monomer is hydroxyethyl acrylate, in the step (3), the products of step (1) and step (2) are mixed in a molar ratio of -OH to -NCO of 1:(0.65-0.95).
9. The UV viscosity reducing adhesive for wafer cutting PO protective film according to claim 1, characterized in that: The photoinitiator comprises 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine; the weight ratio of 1-hydroxycyclohexyl phenyl ketone to 2,4,6-trimethylbenzoyl diphenoxyphosphine is 1:(1.1-1.5).
10. A method for preparing the UV viscosity reducing adhesive for wafer cutting PO protective film according to any one of claims 1 to 9, characterized in that: The preparation steps of the UV viscosity-reducing adhesive include: sequentially adding an acrylate polymer and a photoinitiator into a reaction kettle, and stirring until the photoinitiator is completely dissolved; discharging the material to obtain component A; and mixing component A and component B according to the formula amount when using the UV viscosity-reducing adhesive product. The preparation process was carried out under yellow light conditions.
Citation Information
Patent Citations
Polyurethane type UV viscosity-reducing adhesive based on dimer acid and preparation method of polyurethane type UV viscosity-reducing adhesive
CN118652657A
UV viscosity-reducing glue liquid, UV viscosity-reducing film and display screen module
CN119039890A